DETERMINANTS OF GROSS REGIONAL DOMESTIC PRODUCT IN EASTERN INDONESIA REGION - Istiqomah Istiqomah; Arif Andri Wibowo; Evi Yunianti; Diah Setyorini Gunawan (Faculty of Economics and Business, University of Pasundan, 2019)
Regional income equality has been a major development goal. However, GRDP in Western Indonesia is higher than that in Eastern Indonesia. Therefore, the government should encourage development and increase economic growth in Eastern Indonesia. There are inequalities between those provinces. The purpose of this research is to analyze the effect of labor, domestic investment, foreign direct investment, and government expenditure on GRDP in Eastern Indonesia Region. This study employed regression on panel data of 12 provinces from 2011 to 2016. The results found that labor, domestic investment, foreign direct investment, and government expenditure have positive and significant effect to GRDP. The results imply that all of the independent variables shuld be increas to promote economic growth in The Eastern Indonesia Region.